1978
DOI: 10.1002/xrs.1300070303
|View full text |Cite
|
Sign up to set email alerts
|

Modifications to an electron microprobe to aid in the determination of low atomic number elements

Abstract: The design and installation of a cold trap system is described specifically with reference to its use in ameliorating analysis for low atomic number elements. This trap has been mounted aon an A.R.L. EMX instrument and its use in the analysis of carbon has been investigated. This paper also discusses the metallurgical and metallographic preparation of standards for carbon analysis along with matrix correction procedures for quantitative analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Previous studies have suggested that cooling a cold finger to the temperature of LN 2 was not required for effective decontamination. Indeed, temperatures in the range of −15 to −70°C are found to be effective for cold fingers of different geometries and distances from the sample (Ennos, 1954; Komoda & Morito, 1960; Ranzetta & Scott, 1966; Borile & Garulli, 1978; Hirsch et al, 1994). A detailed study by Hirsch et al (1994) used a cold finger with the geometry of a cage surrounding, but not in contact with, the sample and cooled by LN 2 to varying temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that cooling a cold finger to the temperature of LN 2 was not required for effective decontamination. Indeed, temperatures in the range of −15 to −70°C are found to be effective for cold fingers of different geometries and distances from the sample (Ennos, 1954; Komoda & Morito, 1960; Ranzetta & Scott, 1966; Borile & Garulli, 1978; Hirsch et al, 1994). A detailed study by Hirsch et al (1994) used a cold finger with the geometry of a cage surrounding, but not in contact with, the sample and cooled by LN 2 to varying temperatures.…”
Section: Introductionmentioning
confidence: 99%